Sakralitas Relasi sebagai Respon Kegiatan Industri berdasarkan Konsep Human Ecological Triangle - Hasibuan, Ricky Pramono; Harianja, Mikael (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
Industrial activity is often perceived as a threat to environmental sustainability and sociocultural order, especially when it involves the exploitation of indigenous lands and resources. One case that has led to prolonged conflict is the operation of PT Toba Pulp Lestari (TPL) in Toba Regency, which has significantly affected the local ecosystem and the social relations of the Batak Toba community. This article aims to offer an ethical and theological framework based on the concept of sacred relationality within Batak Toba culture as a critical and constructive response to industrial realities. Using a qualitative descriptive analytical approach, the study is carried out in three stages: an empirical assessment of the social and ecological impacts of TPL’s operations, a theoretical exploration of the Human Ecological Triangle, and contextual theological reflection that integrates public theology with the local value system of Dalihan na Tolu. The findings reveal that sacred relationality, understood as the mutual connection between humans, nature, and the Divine, provides a normative foundation for developing an industrial order that is just, sustainable, and oriented toward the integrity of creation and the dignity of local communities. This relational model rejects exploitative frameworks and affirms the importance of collective responsibility in shaping a just public sphere.